The Effect of Local Community Support Toward Sharia Tourism in Central Maluku Regency - Shalihah, Mar'atun (EQUILIBRIUM, 2022)
This research aims to analyze the local community’s supported influence based on Sharia Tourism Development in the Central Maluku Regency. Some variables are affected by this research, such as negative and positive perceptions of local residents toward the economy, society, and environment around the population. The methodology of this research is quantitative research which uses an explanatory method. There are around 51 participants as samples. Those samples are chosen from Mamala and Morella villages directly involved in tourism activities. The data is processed and analyzed using SEM PLS ver.3 Software. Results of the study found that: the social impact had a positive and significant impact on local community support for sharia tourism development, and the negative impact had a negative and significant impact on the support for sharia tourism development. In contrast, the economic and environmental impact had a positive but not significant impact on the population support local to the development of sharia tourism